2009
DOI: 10.32725/jab.2009.008
|View full text |Cite
|
Sign up to set email alerts
|

Gold and nano-gold in medicine: overview, toxicology and perspectives

Abstract: Nano-technology has entered the field of medicine in recent decades and many of the nanomaterials developed have already had a high impact on health care. Among nanomaterials, gold nanoparticles (GNPs) and gold quantum dots (QDs) are receiving significant attention because their unique physical, chemical and biological properties are quite different from the bulk of their counterparts. In this article, after a brief historical overview, the use of gold and nano-gold in medicine is reviewed, analyzed, and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
75
0
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 157 publications
(80 citation statements)
references
References 94 publications
(78 reference statements)
2
75
0
3
Order By: Relevance
“…Furthermore, gold is usually prescribed for various joints pain conditions (Panyala et al, 2009). This added advantage along with its own potent analgesic and muscle relaxant properties compared to the leaves extract and diclofenac sodium, greatly promotes the use of Salix alba gold nanoparticles as replacement herbal therapy for the clinical management of different pain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, gold is usually prescribed for various joints pain conditions (Panyala et al, 2009). This added advantage along with its own potent analgesic and muscle relaxant properties compared to the leaves extract and diclofenac sodium, greatly promotes the use of Salix alba gold nanoparticles as replacement herbal therapy for the clinical management of different pain conditions.…”
Section: Discussionmentioning
confidence: 99%
“…GNPs have attracted great attention due to their unique electronic, optical, thermal, chemical, and biological properties and their potential catalytic applications in various fields such as biology, medicine, physics, chemistry, material science, and other interdisciplinary fields (Panyala et al 2009). Although physicochemical properties of nanoparticles are well studied, their biological properties largely remain unexplored (Saritha et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Previous reviews indicated that carbon nanotubes would produce lung damage and their toxicity was much stronger than the carbon black [2]. Nano-gold widely used in the immunoassay and molecular recognition has different levels of toxicological effects for organisms [3], and the toxicity of various forms of nano-crystalline TiO 2 to the lung was significantly different [4], which has been confirmed. Quantum dots (QDs) as a new inorganic material have offered such significant advantages as optical labels with high fluorescence quantum yields, stability against photobleaching, and narrow-symmetrical emission spectrum, which has potential value in cell imaging, tumor markers, ion detection and bio-molecular interaction research [5][6][7].…”
Section: Introductionmentioning
confidence: 91%